LINC01410 Knockdown Suppresses Cervical Cancer Growth and Invasion via Targeting miR-2467-3p/VOPP1 Axis - Liu, Fengjuan (Cancer Manag Res, 2020)
BACKGROUND: Long noncoding RNAs have essential roles in human diseases, including cancer. Our work aims to assess the function and mechanisms of LINC01410 in cervical cancer (CC) development. METHODS: Expression analyses were performed using qRT-PCR. Proliferation was determined through CCK8 and colony formation assays. Cell migration and invasion were determined by Transwell assay. The interactions among LINC01410, miR-2467-3p and VOPP1 were analyzed via luciferase reporter assay. RESULTS: LINC01410 was upregulated in CC tissues and cell lines. LINC01410 upregulation correlated with poor prognosis. LINC01410 silencing suppressed proliferation, migration and invasion of CC cells. LINC01410 was the sponge for miR-2467. And LINC01410 promoted VOPP1 expression through inhibiting miR-2467. CONCLUSION: Our findings demonstrated that LINC01410 contributed to CC progression through regulating miR-2467/VOPP1 axis and suggested that LINC01410/miR-2467/VOPP1 cascade may be a potential therapeutic target.